Pharmacological and Therapeutic Applications of Scorpion Venom and its Components: A Review - Yelmame, Shankar S.; Nandyala, Srinivas; Targe, Indrayani K.; Kamble, Sarika M.; Borse, Laxmikant B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Scorpions are ancient creatures from the class Arachnida and order Scorpionida, with around 1,500 species. They have preserved their morphology over millions of years, making them highly successful. When threatened, scorpions release venom containing a mix of toxins, including neurotoxins, cardiotoxins, nephrotoxins, and others. Scorpion stings are more often fatal than snake bites, with deadly species belonging to the Buthidae family, which has about 500 species. The venom causes a range of reactions, from mild skin irritation to severe neurological and cardiovascular issues. Species within the same phylogenetic group tend to have similar immunological properties. The venom's effects can result from a combination of toxins working together. Lethal species include Buthus, Parabuthus, Mesobuthus, Tityus, Leiurus, Androctonus, and Centruroides. Beyond their dangers, scorpion venoms have beneficial properties, including antimicrobial, anti-insect, and anticancer effects. These properties make scorpion venom useful in pest control, infection treatment, and cancer therapies. Scorpion venom consists of a variety of bioactive compounds, featuring disulfide-bridge peptides that are essential for their structural stability and function, as well as non-disulfide-bridge peptides that contribute to the venom's diverse pharmacological properties.